Voice and Justification: Their Influence on Procedural Fairness Judgments - Bies, Robert J.; Shapiro, Debra L. (Academy of Management Journal, 1988)
The article discusses a study which examines whether voice and justification affect unfavorable decisions in job recruitment and budget decision-making. A discussion is presented about the influence of decision-maker justification on people's judgments of procedural fairness and job recruitment decision making. Details related to the reaction of subordinates to an unfavorable budget decision are presented. The article also mentions the effects of voice and justification on procedural justice proceedings.